Prostaglandin E2 receptors as therapeutic targets in renal fibrosis - Henricus A.M. Mutsaers; Rikke Nørregaard (The Korean Society of Nephrology, 2022)
Prostaglandin E2 (PGE2), a lipid mediator produced by the cyclooxygenase enzyme system, is the main prostaglandin in the kidney. PGE2 is involved in various physiological and pathophysiological processes in the kidney, including renal hemodynamics, water and salt balance, and renal fibrosis-a key pathological feature of progressive kidney diseases. PGE2 functions by binding to four G-protein-coupled EP receptors (EP1 to EP4), which stimulate different intracellular signaling pathways. The intrarenal distribution of the four EP receptors as well as the different downstream signaling pathways associated with each receptor give rise to the distinct functional consequence of activating each receptor subtype. This review summarizes the current data on the renal expression of the four EP receptors and delineates the role of each receptor in renal fibrosis.